Re-Writing Her Story: Identity in Toni Morrison’s Beloved and Assia Djebar’s Fantasia between the Interplay of Historical Legacy and Textual Representation - AFILAL, Malika (International Journal of Language and Literary Studies, 2025)
The present paper discusses how Assia Djebar’s Fantasia: An Algerian Cavalcade and Toni Morrison’s Beloved make testimony to historical truth in their representation of feminine identity in two historical contexts: colonialism in Algeria and Racism in America. In the postmodern, postcolonial novels, the African American Morrison and the Algerian Francophone Djebar rewrite two phases of human history, aiming to form, transmit and represent a true historical reality and consciousness through blurring fact and fiction. Djebar revisits the official history of colonialism and the Algerian War of decolonization from France; Morrison, on the other hand, rewrites the history of slavery in antebellum America. Drawing on Linda Hutcheon’s theory, “I investigate how both novelists resurrect the past and develop fictive strategies in seeking to represent a historical truth that corrects the misrepresentation of feminine identity. Both works problematize the question of representation and truth from the standpoint of working-class, marginalized women, namely the Black/African-American and the Arab/Algerian women. While Djebar and Morrison engage with official history shaping each period, they deploy and adopt most of the central tenets and politics associated with the postmodern historical novel, which are in congruity with what Linda Hutcheon calls "historiographic metafiction," a product of both the postcolonial and the postmodern era. In doing so, both writers excavate the archive in search of truth and disclaim the post-structuralist assumption that postmodern narrative is ahistorical.